Case report: Ghost cell odontogenic carcinoma in a dog: diagnostics and surgical outcome - Kim, Chun-Geun; Lee, Ga-Won; Kim, Hyun Sil; Han, Seung-Yong; Han, Dawool; Park, Hee-Myung (Frontiers in Veterinary Science, 2023)
A 6-year-old spayed female Poodle presented with a mandibular mass. Radiographic examination revealed osteolysis from the right mandibular canine to the fourth premolar, along with horizontal bone loss and dorsal displacement of the right mandibular first and second premolars. Skull cone beam computed tomography revealed osteolysis at the level of the right mandibular canine and fourth premolar. A destructive bone lesion was observed in the apical area of the right mandibular canine, with mass invasion of the interradicular bone of the right mandibular first molar near the mandibular canal. Consequently, unilateral total mandibulectomy and skin flap surgery were performed. Histopathological examination revealed poorly demarcated and infiltrative neoplastic epithelial cells that formed small islands and trabeculae. Neoplastic cells exhibited the malignant features of cytological atypia and high mitotic activity. Furthermore, the neoplastic epithelial cells frequently showed ghost cell changes and were diagnosed as ghost cell odontogenic carcinoma (GCOC). The dog was followed up for 1 year, during which no severe complications or local recurrence was observed, except for slight mandibular drift, tongue protrusion, and drooling. This case report describes the clinical features, diagnostic imaging, and histologic features of an unreported GCOC in a dog and the favorable outcome following surgical resection.